A Kajian Morfologi dan Sifat Fisika Tanah Pada Lahan Pasca Tambang Galian C - Muhammad Asril H. Pajula; Adnan Sofyan; Erwin Ladjinga; Asrul Dedy Ali Hasan (Jurnal Penelitian Pendidikan Geografi, 2024)
Kalumata is one of the sub-districts in the City of Ternate which is also the place where excavation C mining activities take place with the type of mining of minerals in the form of volcanic sand when referring to the geological formations from the geological map. Activity results in changes not only in land conversion but also in the condition of the physical properties of the soil. This study aims to determine the morphology and physical properties of the soil in post-mining excavation C in the Kalumata Village. The results of the research on the morphological characteristics of the three soil profiles in the post-mining area C have uniqueness and similarities. While the physical characteristics of the soil on the three soil profiles in the post-mining area C showed that the soil texture was dominated by the dust fraction, the bulk density tended to be low, the particle density was below the average for mineral soil particle density, high dominant porosity, and the lowest soil water content in the profile. III and the highest in profile I, as well as the fractionation of sand grains in each soil layer from profiles I II, and III, the proportion of sand is almost 100% dominating.